EFFECT OF CAUDAL AND ANTERO-POSTERIOR GLIDE IN THE RANGE OF MOTION OF FLEXION, ABDUCTION AND INTENSITY OF PAIN IN SHOULDER (Fiep Bulletin - online, 2013)
The shoulder is a very complex structure that performs many movements during daily activities, so often overloaded and affected by dysfunctions. Studies have demonstrated the potential and importance of using technical manuals glide in the treatment of shoulder movement for the restoration of articular function. The aim of the study was to evaluate the effects of caudal and antero-posterior glide techniques over the range of flexion and abduction in shoulder, and pain intensity in the same movement. The survey was treated in a clinical trial with a sample of 7 volunteers (3 men and 4 women), age 22 ± 0.7 years, with limited range of motion of flexion and abduction and shoulder pain during the same movements. Treatment consisted of 10 sessions in total of 5 weeks, where all volunteers signed an informed consent form. Were used for treatment a caudal and antero-posterior glide techniques with the volunteers in the position of 0° of shoulder abduction at rest. In the evaluation was checked range of motion using a goniometer and the level of pain intensity during the same movements by visual analog scale (VAS), performed before and after treatment total. Statistical analysis was performed using the Shapiro-Wilk test for normality data, followed by the Wilcoxon test for paired data comparison and not normal, it was considered the value of p
Keywords: Motion; Shoulder; Pain.